The Director - Kehlmann, Daniel, 1975- ([Place of publication not identified] : S & S/Summit Books, 2025)
"G.W. Pabst, one of cinema's greatest directors of the 20th century, was filming in France when the Nazis seized power. To escape the horrors of the new and unrecognizable Germany, he fled to Hollywood. But now, under the blinding California sun, the world-famous director suddenly looks like a nobody. Not even Greta Garbo, the Hollywood actress whom he made famous, can help him. When he receives word that his elderly mother is ill, he finds himself back in his homeland of Austria, which is now called Ostmark. Pabst, his wife, and his young son are suddenly confronted with the barbaric nature of the regime. So, when Joseph Goebbels--the minister of propaganda in Berlin--sees the potential for using the European film icon for his directorial genius and makes big promises to Pabst and his family, Pabst must consider Goebbels's thinly veiled order"
new book 2025 spring.
Keywords: World War, 1939-1945; History; Propaganda, West German; Motion picture producers and directors -- Credits; War -- Fiction